Aberrant Development and Synaptic Transmission of Cerebellar Cortex in a VPA Induced Mouse Autism Model - Wang, Ruanna; Tan, Jiahui; Guo, Junxiu; Zheng, Yuhan; Han, Qing; So, Kwok-Fai; Yu, Jiandong; Zhang, Li (Frontiers in Cellular Neuroscience, 2018)
Autistic spectral disorder (ASD) is one prevalent neurodevelopmental disease that affects multiple brain regions. Both clinical and animal studies are revealing the possible involvement of cerebellum in ASD pathology. In this study, we generated a rodent ASD model by single prenatal administration of valproic acid (VPA) into pregnant mice, followed by cerebellar morphological and functional studies on offspring. Behavioral studies showed that VPA exposure led to retardation of critical motor reflexes in juveniles, and impaired learning in a tone-conditioned complex motor task in adults. These behavioral phenotypes were associated with premature migration and excess apoptosis of granular cell (GC) precursor in cerebellar cortex during early postnatal period, and decreased cell density plus impaired dendritic arborization of Purkinje neurons. On acute cerebellar slices, suppressed synaptic transmission of Purkinje cells were reported in VPA mice. In summary, converging evidences from anatomical, electrophysiological and behavioral abnormalities in VPA mice suggest cerebellar pathology in ASD and indicate potential values of motor dysfunction in the early diagnosis of ASD.